The health care dilemma : lessons from health reform in Europe and America - Belien, Paul, 1959-; Vigilante, Kevin; Centre for the New Europe (Zellik : Centre for the New Europe, 1996)
De hervormingen in Groot-Brittannië, Nederland en de Verenigde Staten worden hier even kritisch ontleed.